2006
DOI: 10.1021/pr0504079
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of the Mode of Antibacterial Action of Silver Nanoparticles

Abstract: Silver nanoparticles (nano-Ag) are potent and broad-spectrum antimicrobial agents. In this study, spherical nano-Ag (average diameter = 9.3 nm) particles were synthesized using a borohydride reduction method and the mode of their antibacterial action against E. coli was investigated by proteomic approaches (2-DE and MS identification), conducted in parallel to analyses involving solutions of Ag(+) ions. The proteomic data revealed that a short exposure of E. coli cells to antibacterial concentrations of nano-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
864
5
18

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,407 publications
(907 citation statements)
references
References 51 publications
20
864
5
18
Order By: Relevance
“…Cho et al [15] reported that the surface of the cell walls of E. coli treated with silver nanoparticles were severely damaged compared to untreated E. coli. Cell wall rupture due to silver ions and silver nanoparticles was reported by Lok et al [33]. The attachment of both silver ions or nanoparticles to the cell wall caused accumulation of envelope protein precursors, which resulted in dissipation of the proton motive force.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Cho et al [15] reported that the surface of the cell walls of E. coli treated with silver nanoparticles were severely damaged compared to untreated E. coli. Cell wall rupture due to silver ions and silver nanoparticles was reported by Lok et al [33]. The attachment of both silver ions or nanoparticles to the cell wall caused accumulation of envelope protein precursors, which resulted in dissipation of the proton motive force.…”
Section: Resultsmentioning
confidence: 90%
“…The attachment of both silver ions or nanoparticles to the cell wall caused accumulation of envelope protein precursors, which resulted in dissipation of the proton motive force. Silver nanoparticles also exhibited destabilization of the outer membrane and rupture of the plasma membrane, thereby causing depletion of intracellular ATP [33]. The mode of action of both silver nanoparticles and silver ions were reported to be similar, although the nanoparticles were reported to be effective at significantly lower concentration than that of the ions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Number of different mechanisms responsible for interaction of metal ions with microorganisms structure has been proposed [21,22], e.g., oxygen associated with silver can react with the sulfhydryl (-S-H) groups on cell wall to form R-S-S-R bonds thus, blocking respiration and causing death of cells. Lok et al [23] have found that the surface of the cell walls of E. coli treated with AgNPs were severely damaged compared to untreated E. coli leading to cell wall rupture due to silver ions. Difference in the mechanisms of antibacterial efficiency in between ZnO and Cu/Ag nanoparticles can explain observed here (see Figs.…”
Section: -P3mentioning
confidence: 99%
“…Although the mechanism(s) by which silver kills cells is not fully understood (Lok et al 2006) there have been many suggestions regarding its mode of action. Ag(I) ions interact with thiol groups of the L-cysteine residue of proteins (Park et al 2009;Cortese-Krott et al 2009;Atiyeh et al 2007;Castellano et al 2007).…”
Section: Introductionmentioning
confidence: 99%